Analysis of Traditional Malay House as a Design Approach for Vertical Dwellings towards Green Design - Misnat, Nordin; Surat, Mastor; Binti Ahmad, Norfazillah (International Journal of Engineering and Technology, 2018)
The dwelling space for the Malays is a reflection of the personality of its inhabitants based on the Islamic religion in the fulfilment of its Syariah. In order to meet these needs comfort, safety, health, peace and aesthetic factors have a close relationship to the well-being of the inner space thus making a home of blessing. Today's residence cannot respond well to the needs of the occupants and is too much influenced from the west. It is contrary to the needs of the local design especially the Malays. Compared to the design of Malay house architecture, this concept and architectural approach have met various aspects in achieving the objectives of its residents. There are many lessons and values gained from it. Designs and ideas based on a nature-based environment are able to maintain the need for the future. The writing of this study discusses the issues and problems of modern-day residential homes focusing on interior space planning towards a green and sustainable design by make an analysis of Malay house architectural designs. The design of Malay house architecture has been proven to address the problems and diversity of its residents' needs in achieving the well-being of life.Â Â